2007
DOI: 10.1007/s10562-007-9046-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic low pressure hydrogenation of acetophenone on Pd/ZnO/ZnAl2O4

Abstract: A PdZn alloy-based catalyst was prepared by impregnation with a Pd salt of the oxides obtained by the thermal decomposition of a Zn-Al hydrotalcite. Two samples were obtained by carrying out the reduction at 373 and 673 K, that were characterized by chemical analysis, powder XRD and TEM. The catalytic activity was tested in the low pressure hydrogenation of acetophenone. The results were compared with those obtained using a conventional palladium catalyst

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…4b; Table 1). Analogously in the hydrogenation of acetophenone over Pd/C catalysts in the liquid phase using hexane as a solvent the main product was ethylbenzene when the reaction temperature exceeded 85°C whereas only 40% ethylbenzene was achieved at 60°C [19].…”
Section: Catalyst Characterization Resultsmentioning
confidence: 99%
“…4b; Table 1). Analogously in the hydrogenation of acetophenone over Pd/C catalysts in the liquid phase using hexane as a solvent the main product was ethylbenzene when the reaction temperature exceeded 85°C whereas only 40% ethylbenzene was achieved at 60°C [19].…”
Section: Catalyst Characterization Resultsmentioning
confidence: 99%
“…Several authors have cited the consecutive reaction characteristics of acetophenone hydrogenation. Lenarda et al [47] reported that the selectivity of phenylethanol decreases from 98 to 56% when the conversion increases from 44 to 99% over Pd on Zn-Al hydrotalcite. The same authors also accounted that the selectivity of phenylethanol decreases from 60 to 0% and the selectivity of ethylbenzene increases from 40 to 91%, when the temperature increases from 333 to 423 K. Chen et al [48] reported that the conversion of phenylethanol to ethylbenzene increases rapidly with the increase in conversion over reduced Pd/SiO 2 catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, ZnAl 2 O 4 spinel has been largely used as catalyst in several reactions such as degradation of gaseous toluene 8 , ethanol steam reforming 9 , hydroformylation and hydrogenation 3,10 , combustion of soot under NO x /O 2 atmosphere 11 , transesterification of vegetable oil 12 and iso-butane combustion 13 . The photocatalytic degradation of organic pollutants in the water such as dye [14][15][16] , phenol 17 and pesticide 18 using different semiconductor materials has attracted much attention recently.…”
Section: Introductionmentioning
confidence: 99%